Experimental fragmentation of pipe bombs with varying case thickness - da Silva, Luciana A.; Johnson, Steve; Critchley, Richard; Clements, Jim; Norris, Karl; Stennett, Christopher (Elsevier, 2019)
Among all the improvised explosive devices (IEDs) known, pipe bombs are one of the most popular devices used by terrorists. They are simple to use, easy to construct and materials are readily available. For this IED, fragmentation is the primary injury mechanism, which makes them a desirable weapon for terrorists aiming to inflict maximum human casualties. Although the investigation of fragmentation pattern is not novel, there is limited data available on pipe bombs performance in the open literature. Therefore, this research is looking at validating results in current literature, which showed limited repetition and weak experimental design so far; by trial with six pipe bombs with two different thickness (3 of each). The pipe bombs consisted of mild steel casing and aluminised ammonium nitrate as the explosive filler. Fragments were collected, with an average recovery of 72%, and measured regarding mass and velocity. The experiment results show a correlation between the pipe thickness and both the size and velocity of fragments.
Keywords: Pipe bombs; Forensic science; Fragmentation